2022
DOI: 10.1007/978-3-031-08848-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Process Monitoring

Abstract: Predictive Process Monitoring [29] is a branch of process mining that aims at predicting the future of an ongoing (uncompleted) process execution. Typical examples of predictions of the future of an execution trace relate to the outcome of a process execution, to its completion time, or to the sequence of its future activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 48 publications
0
9
0
4
Order By: Relevance
“…The PPM research pillar includes 22 surveys [71,72,116,141,154,157,160,167,207,211,216,222,247,256,273,275,281,286,290,297,316,318]. Similar to the surveys in the remaining event prediction pillar, the scope of the existing 22 surveys is limited.…”
Section: Related Surveysmentioning
confidence: 99%
“…The PPM research pillar includes 22 surveys [71,72,116,141,154,157,160,167,207,211,216,222,247,256,273,275,281,286,290,297,316,318]. Similar to the surveys in the remaining event prediction pillar, the scope of the existing 22 surveys is limited.…”
Section: Related Surveysmentioning
confidence: 99%
“…Process mining in RPA processes is not very typical at the moment, however, it can be applied to automated processes for RPA (Egger et al, 2020;Průcha, 2021), where duration rates, bottlenecks and deviations can be identified. With advanced methods of process mining such as predictive process monitoring, enhancing the process data with data from other systems, root-cause analysis and online monitoring, it is possible to gain more valuable insights about the behavior of RPA processes including information why an RPA bot fails, whether the bot fails when executing a particular variant and whether RPA bots can keep up with the queue of cases (Burattin, 2022;Di Francescomarino and Ghidini, 2022;Fahland, 2022;Van Houdt and Martin, 2021). The use of statistical methods in process mining represents the core of process mining.…”
Section: Variability and Spc In Process Miningmentioning
confidence: 99%
“…For instance, organizational mining techniques were developed to focus on resources employed within the process [53]. Moreover, these additional data attributes also play a fundamental role in decision mining [18,47] (see [17]) and predictive process monitoring [19] (see [20]).…”
Section: Additional Data Attributesmentioning
confidence: 99%